2022
DOI: 10.3390/metabo12100968
|View full text |Cite
|
Sign up to set email alerts
|

SmMYB4 Is a R2R3-MYB Transcriptional Repressor Regulating the Biosynthesis of Phenolic Acids and Tanshinones in Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza Bunge is one of the most famous traditional Chinese medicinal plants. The two most important classes of pharmaceutically relevant compounds in S. miltiorrhiza are phenolic acids and tanshinones. The MYB family of transcription factors may efficiently regulate the secondary metabolism in plants. In this study, a subgroup 4 R2R3MYB transcription factor gene, SmMYB4, was isolated from S. miltiorrhiza and functionally characterized using overexpression and a RNAi-mediated silencing. We achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…In jujube, Wen et al (2022) [56] conducted a comprehensive study using metabolite profiling and transcriptomic data analysis on cultivated jujube, which revealed that terpenoids were mainly concentrated in ZjSQS1 (evm.model. Many transcription factors (TFs) have been confirmed roles in regulating terpenes accumulation by affecting the expression of genes related to terpene synthesis in other plants , such as WRKY [59,60], bHLH [61][62][63], AP2/ERF [64][65][66], MYB [67][68][69][70][71], and bZIP [72][73][74], among others. Notable examples of these regulators include PnbHLH1, which controls the biosynthesis of triterpene saponins in Panax notoginseng [61,75], ERF189, an ethylene response factor implicated in the biosynthesis of steroidal glycoalkaloids in potatoes and tomatoes [75,76], and SmERF1L1, which regulates the biosynthesis of tanshinones in Salvia miltiorrhiza Bunge [77].…”
Section: Biosynthesis Of Terpenoids In Jujubementioning
confidence: 99%
“…In jujube, Wen et al (2022) [56] conducted a comprehensive study using metabolite profiling and transcriptomic data analysis on cultivated jujube, which revealed that terpenoids were mainly concentrated in ZjSQS1 (evm.model. Many transcription factors (TFs) have been confirmed roles in regulating terpenes accumulation by affecting the expression of genes related to terpene synthesis in other plants , such as WRKY [59,60], bHLH [61][62][63], AP2/ERF [64][65][66], MYB [67][68][69][70][71], and bZIP [72][73][74], among others. Notable examples of these regulators include PnbHLH1, which controls the biosynthesis of triterpene saponins in Panax notoginseng [61,75], ERF189, an ethylene response factor implicated in the biosynthesis of steroidal glycoalkaloids in potatoes and tomatoes [75,76], and SmERF1L1, which regulates the biosynthesis of tanshinones in Salvia miltiorrhiza Bunge [77].…”
Section: Biosynthesis Of Terpenoids In Jujubementioning
confidence: 99%
“…However, the corresponding transcription factor of ZjSQE is still unclear (Figure 2). Many transcription factors (TFs) have been confirmed to have roles in regulating terpene accumulation by affecting the expression of genes related to terpene synthesis in other plants, such as WRKY [65,66], bHLH [67][68][69], AP2/ERF [70][71][72], MYB [73][74][75][76][77], and bZIP [78][79][80]. Notable examples of these regulators include PnbHLH1, which controls the biosynthesis of triterpene saponins in Panax notoginseng [67,81], ERF189, an ethylene response factor implicated in the biosynthesis of steroidal glycoalkaloids in potatoes and tomatoes [81,82], and SmERF1L1, which regulates the biosynthesis of tanshinones in Salvia miltiorrhiza Bunge [83].…”
Section: Terpenoid Biosynthesismentioning
confidence: 99%